SNAKES AND LADDERS GAME AS A SOLUTION TO REDUCE STRESS BY PARENTING STYLE AS A MEDIATION IN MATHEMATICS SUBJECTS - Hasibuan, Wilda Fasim; Qoriaturrosyidah, Fitri; AlWahab, Putri Annisa; Ananda, Nur Fitri; Hanggara, Yudhi (Universitas Batanghari Jambi, 2024)
Stress in everyday life is normal, but it becomes extraordinary when it occurs during adolescence. There are numerous stressors for adolescents, including academic success in mathematics. Consequently, the purpose of this study is to provide education on snakes and ladders as a means of reducing stress tendencies by mediating mathematics parenting. Before receiving the ladder snake educational treatment, there was no difference in stress tendencies (p < 0.152). Then, regardless of their parenting style, the level of student tension is the same. The inference is that lowering stress tendencies in adolescents cannot be achieved by concentrating on a single causal factor; rather, it is required to look for additional elements that broadly impact stress.